2013
DOI: 10.5858/arpa.2011-0516-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Number and Types of Plasma Samples Necessary for an Accurate Activated Partial Thromboplastin Time–Based Heparin Therapeutic Range

Abstract: , MT(ASCP) N Context.-Monitoring of unfractionated heparin therapy by activated partial thromboplastin time (aPTT) using the ex vivo method for determining the aPTT-based heparin therapeutic range (HTR) is the standard of practice. Many intrinsic and extrinsic factors influence its accuracy.Objective.-To investigate the optimum number and types of samples acceptable for an accurate ex vivo HTR determination.Design.-Values from patients receiving unfractionated heparin are used to determine the HTR by publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The reason for this is unknown but may relate to the patients included in the analysis as a wider range of 1.6-3.0 has been reported [10]. This reflects the lack of specificity of APTT for heparin effect and it is possible that analysis of a larger number of samples is required, as proposed by some authors [17], although others have suggested that 20 may be sufficient [18]. This reflects the lack of specificity of APTT for heparin effect and it is possible that analysis of a larger number of samples is required, as proposed by some authors [17], although others have suggested that 20 may be sufficient [18].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unknown but may relate to the patients included in the analysis as a wider range of 1.6-3.0 has been reported [10]. This reflects the lack of specificity of APTT for heparin effect and it is possible that analysis of a larger number of samples is required, as proposed by some authors [17], although others have suggested that 20 may be sufficient [18]. This reflects the lack of specificity of APTT for heparin effect and it is possible that analysis of a larger number of samples is required, as proposed by some authors [17], although others have suggested that 20 may be sufficient [18].…”
Section: Discussionmentioning
confidence: 99%
“…The overall assessment of the ex vivo HTR method is that the same laboratory generates an accurate HTR if the same reagent lot and instrumentation methodology are used. Although these studies are not performed on all commercially available reagents or instruments but limited to a selection of the 2-3 different reagents, the same results are found [8,19]. Therefore, the basic findings can be applied to all reagents-instrument systems [8,19].…”
Section: Discussionmentioning
confidence: 82%
“…Both assays are calibrated using the manufacturer's calibrators (assigned against the WHO unfractionated heparin standard). In a comparison study of the two heparin assays, no significant difference in the heparin values is noted between assay kits (r = 0.95, slope = 0.99, P = 0.86) [8,19]. No difference in the heparin levels between unfrozen and frozen samples is found (data not shown).…”
Section: Heparin Antifactor Xa Assaymentioning
confidence: 91%
“…However, different investigations demonstrated that standardization between laboratories using aPTT for monitoring UFH therapy is quite poor. Each laboratory should determine their aPTT reagent sensitivity to UFH and establish local heparin TI for every new reagent lot, reagent type or instrument which is very complicated in routine ( 11 , 18 , 19 ). …”
Section: Discussionmentioning
confidence: 99%
“…LMWH use has at least partly suppressed many aPTT testing issues in the context of heparin monitoring and replaced UFH as the preferred option in many clinical situations ( 19 ). As expected, survey respondents from Clinical Hospital Centres and Clinical Hospitals declared to use exclusively anti-Xa assay, while smaller hospital laboratories use aPTT for monitoring LMWH therapy.…”
Section: Discussionmentioning
confidence: 99%